The impact of perception and presence on emotional reactions: A review of research in virtual reality - Julia Elisabeth Diemer; Georg W Alpers; Henrik M Peperkorn; Youssef eShiban; Andreas eMühlberger (Frontiers in Psychology, 2015)
Abstract is inlcuded in the main text file due to technial problems.